Oxidative DNA Damage in Kidneys and Heart of Hypertensive Mice Is Prevented by Blocking Angiotensin II and Aldosterone Receptors - Brand, Susanne; Amann, Kerstin Ute; Mandel, Philipp; Zimnol, Anna; Schupp, Nicole (PLoS ONE, 2014)
Recently, we could show that angiotensin II, the reactive peptide of the blood pressure-regulating renin-angiotensin-aldosterone-system, causes the formation of reactive oxygen species and DNA damage in kidneys and hearts of hypertensive mice. To further investigate on the one hand the mechanism of DNA damage caused by angiotensin II, and on the other hand possible intervention strategies against end-organ damage, the effects of substances interfering with the renin-angiotensin-aldosterone-system on angiotensin II-induced genomic damage were studied.In C57BL/6-mice, hypertension was induced by infusion of 600 ng/kg o min angiotensin II. The animals were additionally treated with the angiotensin II type 1 receptor blocker candesartan, the mineralocorticoid receptor blocker eplerenone and the antioxidant tempol. DNA damage and the activation of transcription factors were studied by immunohistochemistry and protein expression analysis.Administration of angiotensin II led to a significant increase of blood pressure, decreased only by candesartan. In kidneys and hearts of angiotensin II-treated animals, significant oxidative stress could be detected (1.5-fold over control). The redox-sensitive transcription factors Nrf2 and NF-?B were activated in the kidney by angiotensin II-treatment (4- and 3-fold over control, respectively) and reduced by all interventions. In kidneys and hearts an increase of DNA damage (3- and 2-fold over control, respectively) and of DNA repair (3-fold over control) was found. These effects were ameliorated by all interventions in both organs. Consistently, candesartan and tempol were more effective than eplerenone.Angiotensin II-induced DNA damage is caused by angiotensin II type 1 receptor-mediated formation of oxidative stress in vivo. The angiotensin II-mediated physiological increase of aldosterone adds to the DNA-damaging effects. Blocking angiotensin II and mineralocorticoid receptors therefore has beneficial effects on end-organ damage independent of blood pressure normalization.
EVALuna2:25417